EFL STUDENTS' PERSPECTIVES ON THE USE OF CLT IN LEARNING SPEAKING AT SIXTH GRADE SDN CIPETE 2 SERANG - Nita Noviyanti Rahayu; Sheefmy Natwila Puteri (CV. ADIBA AISHA AMIRA, 2024)
This research explores the perspectives of sixth-grade students at SDN Cipete 2 Serang regarding the use of Communicative Language Teaching (CLT) in English Learning. A qualitative descriptive method was used in this research. The results showed that students had a good understanding of the concepts and objectives of CLT, which they acknowledged was more effective than traditional methods. They feel more comfortable and involved in the learning process, although some students still feel nervous when speaking in front of their friends. This method has proven effective in improving students' speaking skills and self-confidence, as well as increasing their interest and motivation in learning English. However, some of the difficulties faced included language and focus barriers during long- lasting activities. Interaction between students, teachers, and classmates increases, creating a more relaxed and supportive classroom atmosphere. Students provide input for improvement, including the use of visual media, a variety of activities, and constructive feedback from teachers.